Heth longquani sp. n.—(Rhigonematomorpha: Hethidae)—obligate commensalistic nematode of camballoid millipede (Spirostreptida: Cambalopsidae) from Viet Nam - Spiridonov, Sergei E.; Đinh, Dung The (Zootaxa, 2023)
A new nematode species, Heth longquani sp. n. (Hethidae, Ransonematoidea, Rhigonematomorpha, Rhabditida) is described from the camballoid millipede, Chonecambala crassicauda from Thanh Hóa province, Viet Nam. The morphological features of this new species were studied with brightfield and scanning electron microscopies. Partial sequences of LSU rDNA and Cox1 mtDNA are provided. The phylogeny of the nematodes of the genus Heth Cobb, 1898 is discussed.